Hubungan Antara Kecanduan Bermain Game Online Dengan Perilaku Agresif - Satria Eka Saputra; Satrio Budi Wibowo; Eko Susanto (Counseling Milenial (CM), 2026)
This study aims to determine the relationship between addiction to playing online games in students of SMK Negeri 2 Metro. This type of research is quantitative correlation, the subjects in this study are students of class XI OTO SMK Negeri 2 Metro. The technique used in this study is correlation with pearson product moment statistical calculations. The instruments used in this study are a questionnaire of addiction to playing online games and a questionnaire of aggressive behavior. The results in this study indicate a very significant positive relationship between addiction to playing online games and aggressive behavior.